PENUGASAN DALAM DUE DILIGENCE - Sayuthi Sayuthi (Jurnal Telaah dan Riset Akuntansi, 2010)
The objective of this study is to know what auditors did in due dilegence task and how auditors implement their responsibilities  in that rule.  This study found that there are the four main activities, 1) preliminary actions, relating with preparation for due diligence, particularly before doing due diligence, 2) fieldwork, discussing activities in company where auditors plan to make audit procedure, 3) reporting, involving activities with summarizing audit results in official report, and finally 4) debriefing, relating with having a meeting with client and auditor team, and then discussing about the audit result from due diligence.The rule and responsibilities of auditor in due diligence task arise because of business needs. Company or auditors’ clients can’t make their decision without recommendation from auditors in due diligence. For example, in merger  or joint venture process, company needs the auditors’ assessment in face uncertainty. Initial Public Offerring (IPO), as evidence for this necessity, the government rules require emiten to do due diligence in order to listing in Indonesian Capital Market (BEI). Keywords: due diligence, debrifing, merger, joint venture, and IPO